2009
DOI: 10.4012/dmj.28.197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of attrition, prior acid-etching, and cyclic loading on the bond strength of a self-etching adhesive system to dentin

Abstract: The purpose of this study was to evaluate the effects of dentin attrition, phosphoric acid etching, and cyclic loading on the microtensile bond strength (μTBS) of a self-etching adhesive system to dentin. Flat dentin surfaces of human molars were assigned to eight experimental groups based on those with or without attrition, prior acid-etching, and cyclic loading. Resin composite paste was placed and polymerized after the bonding procedure according to manufacturer's instructions. The specimens were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
0
1
3
Order By: Relevance
“…Based on the result obtained in this study, this pretreatment of the dentin surface did not adversely affect the dentin bond strength. The µTBS value of Clearfil SE Bond to dentin with this pretreatment was 52.7 MPa in this study, which was significantly higher than the 29.2 MPa obtained for the same adhesive without pretreatment in a previous study 28) . This significant difference in µTBS value hence suggested that pretreating the dentin surface with 10% NaClO gel followed by alternate irrigation with 3% H2O2 and 6% NaClO might be effective in increasing the dentin bond strength of self-etching primer systems.…”
Section: Discussioncontrasting
confidence: 48%
“…Based on the result obtained in this study, this pretreatment of the dentin surface did not adversely affect the dentin bond strength. The µTBS value of Clearfil SE Bond to dentin with this pretreatment was 52.7 MPa in this study, which was significantly higher than the 29.2 MPa obtained for the same adhesive without pretreatment in a previous study 28) . This significant difference in µTBS value hence suggested that pretreating the dentin surface with 10% NaClO gel followed by alternate irrigation with 3% H2O2 and 6% NaClO might be effective in increasing the dentin bond strength of self-etching primer systems.…”
Section: Discussioncontrasting
confidence: 48%
“…As técnicas estudadas para seu armazenamento até o uso vão desde o congelamento 69 , refrigeração 49 até o armazenamento em temperatura ambiente. Para tanto, pode-se utilizar substâncias tais como água destilada 18,29,49,56,58,59 solução fisiológica 34 , timol 29,33,50,62,67 , e cloramina t 6,9,12,15,16,17,18,20,24,27,30,[37][38][39]41,[44][45][46]55,61,64,71,72 . Os protocolos com timol e cloramina T são indicados para evitar crescimento bacteriano, sem alterar a morfologia do substrato 33, 50,62 .…”
Section: Substância Para Armazenamento Da Amostraunclassified
“…O protocolo de armazenamento mais atual para os dentes humanos é a utiliza-ção da cloramina T a 0,5%, sob refrigeração (4°C) 6,9,12,15,16,17,18,20,24,27,30,[37][38][39]41,[44][45][46]55,61,64,71,72 , mas também é comum o armazenamento em água destilada 18,29,49,56,58,59 . No entanto, um estudo recente de Mobarak et al 29 (2010) concluiu que o tempo e a forma de armazenamento não afetam os resultados obtidos no teste de microtração, ao comparar dentes recém-extraídos, dentes armazenados por 2 anos em cloramina-T a 0,5% sob refrigeração e dentes secos posteriormente reidratados no momento da execução do experimento.…”
Section: Substância Para Armazenamento Da Amostraunclassified
See 1 more Smart Citation